2021
DOI: 10.1021/acs.energyfuels.1c01021
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Characteristics and Mechanism of Hg0 Removal by NaClO2 in Limestone Slurry

Abstract: In this study, the Hg0 removal characteristics of NaClO2 in limestone slurry were investigated in a bubbling reactor. The effects of slurry conditions (pH, temperature, and Cl– concentration) and flue gas components (NO, SO2, HCl, etc.) on Hg0 removal activity and efficient Hg0 removal duration were explored. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were used to characterize the solid products prepared under different conditions. It was found that NaClO2 exhibited superior Hg0 removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…36,39 Our previous study also found that the chemisorbed oxygen species was responsible for Hg 0 oxidation. 32,40 However, the O α ratio increased when the catalyst was pretreated in the presence of NO. This might be because the gaseous NO could adsorb on the catalyst surface to form adsorbed NO or other substance containing O species, thus increasing the chemisorbed oxygen species.…”
Section: Xps Characterizationsmentioning
confidence: 99%
“…36,39 Our previous study also found that the chemisorbed oxygen species was responsible for Hg 0 oxidation. 32,40 However, the O α ratio increased when the catalyst was pretreated in the presence of NO. This might be because the gaseous NO could adsorb on the catalyst surface to form adsorbed NO or other substance containing O species, thus increasing the chemisorbed oxygen species.…”
Section: Xps Characterizationsmentioning
confidence: 99%
“…In the past ten years, multifarious wet free-radical AOTs, which mainly comprises photochemical oxidation, electrochemical oxidation, metal ion-activated peroxide oxidation, thermal activation peroxide oxidation, metal oxide-activated peroxide oxidation, and so forth have been developed widely for oxidizing Hg 0 in flue gas. Among these potential candidates, these Fenton oxidation technique demonstrates a good development and industrial application prospect due to a simpler system and smaller device requirement. ,, However, the traditional Fenton oxidation technique has low yield in free radicals owing to a low Fe 2+ /Fe 3+ cycle rate, severe side reactions, and low utilization rate in free radicals, thereby causing low pollutant treatment capacity and high reagent consumption cost. ,− Thus, exploring a new, simple, and effective method to improve these shortcomings in the traditional Fenton activation system is highly desired in this area.…”
Section: Introductionmentioning
confidence: 99%